2017
DOI: 10.1016/j.ijmedinf.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

“Think aloud” and “Near live” usability testing of two complex clinical decision support tools

Abstract: Objectives Low provider adoption continues to be a significant barrier to realizing the potential of clinical decision support. “Think Aloud” and “Near Live” usability testing were conducted on two clinical decision support tools. Each was composed of an alert, a clinical prediction rule which estimated risk of either group A Streptococcus pharyngitis or pneumonia and an automatic order set based on risk. The objective of this study was to further understanding of the facilitators of usability and to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 31 publications
0
72
0
1
Order By: Relevance
“…5 usability issues may be detected and addressed prior to full-scale implementation [31] in other to reduce attrition rates. [26,32,33]…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…5 usability issues may be detected and addressed prior to full-scale implementation [31] in other to reduce attrition rates. [26,32,33]…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…By applying this method, the thoughts, interactions, and cognitions process are verbalized while the tasks are completed [24]. The usability sessions were conducted by representing written scenarios that described patients with different conditions to participants [25,26].…”
Section: Usability Evaluationmentioning
confidence: 99%
“…Shin et al (2017) presented a study that validated a model using data collected in a time-series study of consumer use of online HIS in a user oriented context. Richardson et al (2017) Robinson et al (2014) identified the importance of patient portals for patients' interaction with healthcare organizations and to view information. The purposes are categorised as informational, medical, logistical, or social.…”
Section: Smart Livingmentioning
confidence: 99%